2016
DOI: 10.1103/physrevb.94.045127
|View full text |Cite
|
Sign up to set email alerts
|

Parafermion chain with2π/kFloquet edge modes

Abstract: We study parafermion chains with Z k symmetry subject to a periodic binary drive. We focus on the case k = 3. We find that the chains support different Floquet edge modes at nontrivial quasienergies, distinct from those for the static system. We map out the corresponding phase diagram by a combination of analytics and numerics, and provide the location of 2π/3 modes in parameter space. We also show that the modes are robust to weak disorder. While the previously studied Z2-invariant Majorana systems posesses a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…In Ref. 14 it was shown that edge modes lead to approximate degeneracies in the Floquet spectrum of a particular clean, interacting system. However the implications of this for the dynamics of the modes and their robustness to heating was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 14 it was shown that edge modes lead to approximate degeneracies in the Floquet spectrum of a particular clean, interacting system. However the implications of this for the dynamics of the modes and their robustness to heating was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…After the experimental clarification that two zero-energy Majorana modes can be localized at the edges of a one-dimensional fermionic wire [6,7], the possibility of localizing parafermionic modes, and letting them interact, is currently under deep investigation. These excitations cannot appear in strictly one-dimensional spinless fermionic systems [8,9], but may emerge at the edge of a two-dimensional fractional topological insulator coupled to alternating ferromagnetic and superconducting materials [5,[10][11][12][13][14][15], as well as in other nanostructures or models [16][17][18][19][20][21][22][23][24].In these setups, one-dimensional chains of interacting parafermions arise, which, in certain circumstances, display TO and edge Z N parafermionic modes [5,[25][26][27][28][29][30][31][32][33][34]. Such edge modes are called strong when they commute with the Hamiltonian [35] and thereby generate a N -fold degeneracy in the entire spectrum, and weak when the commutation property and associated degeneracy are restricted to the ground state manifold.…”
mentioning
confidence: 99%
“…In these setups, one-dimensional chains of interacting parafermions arise, which, in certain circumstances, display TO and edge Z N parafermionic modes [5,[25][26][27][28][29][30][31][32][33][34]. Such edge modes are called strong when they commute with the Hamiltonian [35] and thereby generate a N -fold degeneracy in the entire spectrum, and weak when the commutation property and associated degeneracy are restricted to the ground state manifold.…”
mentioning
confidence: 99%
“…Recently, time periodic modulations of topologically trivial systems, often realized via light-matter interaction, have emerged as an interesting way of obtaining topological phases, often richer than their static counterparts [33][34][35][36][37][38][39][40][41][42][43][44][45] and effects of interaction and disorder have also been explored [46][47][48][49][50][51]. Such protocols have also been complemented with their experimental realizations.…”
mentioning
confidence: 99%